L’indispensable accès à internet à la campagne : la capillarisation de l'information au Brésil et en France - Mait Bertollo (Confins)
The research being carried out on information objects used in the Brazilian countryside, in the first step, highlights their growing participation in activities that result in a potential increase in production. In the agribusiness sector, these systems and technical objects such as sensors, equipment and machines, digitally connected through the Internet of Things (IoT), allow large volumes of data of the most varied types to be shared with greater fluidity, feeding countless systems for the control of various stages of the different productive spatial circuits. With the advent of the IoT, the pace of data growth and its speed have increased exponentially, requiring rural establishments and each production stage to be connected to telecommunications networks. An analysis of the players involved in the development, dissemination and connection of these systems and their impact on agricultural production can provide answers on the use of IoT in the Brazilian countryside and also in the French countryside, in the second step, as a possibility to mitigate the disparities between large and small producers through the dissemination and trivialization of the use of information technologies and internet infrastructures in the context of family farming, taking advantage of the diverse knowledge of small and medium-sized producers, actions in cooperatives and the strengthening of food production and agroecology.